Does Collective Responsibility for Performance Alter Party Strategies? Policy-Seeking Parties in Proportional Systems. Issue 1 (14th May 2012) - Adams, James; Ezrow, Lawrence; Merrill, Samuel; Somer-Topcu, Zeynep
Abstract: Adams and Merrill have developed a model of policy-seeking parties in a parliamentary democracy competing in a PR electoral system, in which party elites are uncertain about voters' evaluations of the parties' valence attributes such as competence, integrity and charisma. This article extends that model to situations where voters hold coalitions of parties collectively responsible for their valence-related performances, such as how voters evaluate governing parties' competence in handling issues like the economy, crime and foreign policy crises. It may also be relevant to voters' evaluations of proto-coalitions of opposition parties. Computations suggest the central substantive conclusions reported in Adams and Merrill extend to this generalized model, and that collective responsibility enhances coalition members' incentives to converge to similar policy positions but depresses their prospects of achieving their policy objectives.